CHEMICAL COMPOSITION AND ANTIOXIDANT ACTIVITY OF TROPICAL BROWN ALGAE Padina australis FROM PRAMUKA ISLAND, DISTRICT OF SERIBU ISLAND, INDONESIA - Joko Santoso; Fitriany Podungge; Heru Sumaryanto (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
The proximate composition, dietary fiber, and total phenol contents as well as antioxidant activity of tropical brown alga Padina australis collected from the Pramuka Island, District of Seribu Island, Indonesia during the rainy season of 2011 were determined in order to evaluate their potential nutritional value and activity of natural antioxidant compound. The content of ash, protein, and fat were 22.26, 10.76, and 4.17 g/100 g dry matter, respectively; whereas the amounts of soluble, insoluble, and total dietary fibers were 8.4, 5.4, and 13.8 g/100 g, respectively. Methanol extract of P. australis contained the highest total phenol of 246.1 mg GAE/1000 g dry sample. The extract also had the highest activity on DPPH radical scavenging, measured by IC50 of 267.1 ppm. Both the total phenol and IC50 value extracts decreased in the following order: methanol > ethyl acetate > n-hexane.Keywords: antioxidant, dietary fiber, DPPH-scavenging, Padina australis, proximate composition